Improvement of nutritive value of acacia mangium bark by alkali treatment - Elizabeth Wina; Toto Toharmat; Widia Astuti (Jurnal Ilmu Ternak dan Veteriner, 2001)
Bark, especially from Acacia mangium is a by-product from wood processing industries that commonly found in Indonesiaand in big amount will cause environmental problems. One of the alternatives to utilize bark is for animal feed. The aims of this experiment are to improve the nutritive value of bark by alkali treatments (urea and sodium hydroxide) and to determine the level of substitution of elephant grass by bark. The experiment consisted of 3 in vitro studies and 1 in sacco study. In vitro studies consisted of 1) the use of urea or NaOH by wetting and incubation-method, 2) the use of different concentration of Na OH (0-4%) by soaking method, 3) determination of substitution level of elephant grass by treated bark. In sacco study was conducted at 0, 6, 12, 24, 48 and 72 hours of incubation to compare the degradation of treated bark to elephant grass. The results show that urea treatment did not improve DM or OM digestibilities of bark. Soaking bark in 4% NaOH solution was more effective than wetting and incubation-method in improving in vitro digestibility. (49.26% vs19.56% for soaking and dry-method, respectively). In sacco studyl shows that treated bark had a very high solubility at 0 hour incubation but the degradation at 72 hours incubation was not significantly different from that of 0 hour incubation. The gas produced at in vitro study of treated bark was very low indicated that there was no degradation of bark at all. The level of substitution of elephant grass by treated bark up to 30% gave a non-significant digestibility value to that of 100% elephant grass. In conclusion, bark after tannin-extraction was a better feedstuff for animal feed. The soaking method in 4% NaOH solution improved the digestibility of bark significantly and the level of substitution of elephant grass by treated bark was 30%.   Key words: Bark, acacia mangium, urea, sodium hydroxide, digestibility